2005
DOI: 10.3748/wjg.v11.i25.3966
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hepatocellular carcinoma with bile duct tumor thrombi

Abstract: Abstract Abstract AbstractAIM: To study the surgical treatment effect and outcome of hepatocellular carcinoma (HCC) with bile duct tumor thrombi (BDTT). METHODS:Fifty-three consecutive HCC patients with BDTT admitted in our department from July 1984 to December 2002 were reviewed retrospectively. The clinical data, diagnostic methods, surgical procedures and outcome of these patients were collected and analyzed. RESULTS:One patient rejected surgical treatment, 6 cases underwent percutaneous transhepatic cholan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 17 publications
0
38
1
Order By: Relevance
“…Peng et al [8] also reported that it is easy to remove BDTT because most of thrombi do not tightly adhere to the wall of the bile duct. In our study, the tumor thrombi were always fragile, fleshy, grayish-white, and located along the biliary tree, which was in agreement with the reports of Edmondson some 50 years ago [21].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Peng et al [8] also reported that it is easy to remove BDTT because most of thrombi do not tightly adhere to the wall of the bile duct. In our study, the tumor thrombi were always fragile, fleshy, grayish-white, and located along the biliary tree, which was in agreement with the reports of Edmondson some 50 years ago [21].…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have demonstrated that BDTT was often present when the primary tumor was very small. Peng et al [8] reported that in 53 cases of HCC with BDTT, the primary tumor was not found in seven cases, and the diameter of the primary tumor was less than 5 cm in 25 cases. Qin et al [9] reported that in 34 cases of such tumors, the diameter of the primary tumor was 6.4 ± 2.5 cm and all of the primary tumors had no capsule, unclear tumor margins, and an invasive pattern of growth.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations